EXCLUSION OF THE CONTENT OF OBJECTS AND THE ACCOUNTING METHOD IN THE CONDITIONS OF DIGITAL ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The scientific article is devoted to the digitization of the Ukrainian economy and its impact on the information security of enterprises. The digital economy is the model of interaction of all participants in economic processes, which is based on the use of modern electronic communication channels, methods of recording and storing information, using electronic document management, maximum automation of business processes within the enterprise and in relations with contractors and government agencies. In the system of information provision of socio-economic processes, traditionally significant role is played by accounting with its function of collecting, processing and providing economic information about the activities of the business entity. The article focuses on the relevance of the question of rethinking the role and place of accounting in the information system, in particular in the transition to a digital economy, research into the change of its content, methodological and conceptual foundations under the influence of technological possibilities of digitalization and requirements for information content.The activities of an enterprise, a company employing digital technology, are more effective than traditional, in terms of labor productivity and possible costs per unit of production. In a digital economy, accounting, while maintaining its relevance and demand for the product created, should become a clear component of the system of receiving, processing, and transferring economic information.In connection with this, there was a need for the introduction of electronic document management (EDM), which is based on an electronic document. Digitization in accounting is impossible without EDM, the advantage of which is accelerated rotation of money and resource savings.